KONSEP MANAJEMEN PENDIDIKAN YANG TERKANDUNG DALAM AYAT – AYAT SURAT AL INSYIRAH - Anggraini, Desi Anggraini (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The aim of writing this article is to explain the concept of educational management contained in the verses of Surah al-Insyirah. The method for writing this article is literature study. This scientific journal presents material related to the management concepts contained in Surah al-Isyirah. then analyze it and present it systematically in this paper. The results of this article present the importance of Islamic education management in developing capacity as an educator and understanding the concepts of Islamic education in the verses of Surah al Isyirah as well as case studies in the concept of education management